Modeling of alkali-silica reaction in a two phased material model - Itam Z.; Husain H. (Penerbit UTM Press, 2023)
Alkali-silica reaction causes major problems in concrete structures due to the rapidity of its deformation. Factors that affect ASR include the alkali and silica content, relative humidity, temperature and porosity of the concrete, making the relationship a complex phenomenon to be understood. Hence, the finite element technique was used to build models to study the damage propagation due to ASR. Seeing that ASR initializes in the mesoscopic regions of the concrete, the damage model for ASR at the mesoscale level is studied. The heterogeneity of the mesoscale model shows how difference in material properties between aggregates and the cementitious matrix facilitates ASR expansion. With this model mesoscopic, two-phased material model, the ASR phenomenon under thermo-chemo-hygro-mechanical loading can be understood. 2015 Penerbit UTM Press. All rights reserved.